Development and validation of a responsible leadership scale - Simões, L. M.; Duarte, A. P. (Dialogues in Organizational Behavior: Book of Abstracts, 2024)
Climate change, technological threats and inequality are some of the issues that the world currently faces, which directly or indirectly affect and are affected by the diferente organizations that exists. Considering this complex and challenging environment, organizations need to focus on the needs outside of their immediate scope, providing changes both internally and externally. Besides the economic aspect, social and environment considerations need to be integrated into the decision-making process and organizations’ goals. These changes in the way organizations run their businesses require leaders that have attention for the triple-bottom line, as well as closer relationships with the different stakeholders to have a better understanding of the issues currently happening. To measure the extent to which leaders present this set of characteristics, we are currently developing and validating a measure of responsible leadership.